Effects of temperature, pH and O2 on the removal of hydrogen sulfide from biogas by external biological desulfurization in a full scale fixed-bed trickling bioreactor (FBTB) - Naegele, Hans-Joachim; Lindner, Jonas; Merkle, Wolfgang; Lemmer, Andreas; Jungbluth, Thomas; Bogenrieder, Claus (International Journal of Agricultural and Biological Engineering, 2013)
Hydrogen sulfide (H2S) is a critical component of biogas formed under anaerobic conditions by sulfur and sulfate reducing bacteria from animal manure and renewable energy crops. H2S causes high corrosion in equipment, has a negative environmental impact, inhibits the biogas formation process and is furthermore odorous and toxic. Although several methods for internal and external desulfurization found their way into practice and had been explored at laboratory scale, no data were available on the performance of such methods in full scale practice, especially for an external fixed-bed trickling bioreactor (FBTB). The effects of temperature, pH and air ratio on H2S removal efficiency (RE) were studied. The study was conducted at a research biogas plant with a given output of 96 m3 biogas per hour, and an H2S concentration ranging between 500 ppm and 600 ppm (1 ppm=1 cm3/m3) on average. The FBTB column has been designed to hold a packing volume of 2.21 m3 at a gas retention time of 84 seconds being loaded at an average of 32.88 g H2S/(m3?h). The highest H2S RE of 98% was found at temperatures between 30